HUBUNGAN KETERAMPILAN MENGAJAR GURU DENGAN MINAT BELAJAR SISWA SDN PAGIRIKAN 1 KECAMATAN PASEKAN KABUPATEN INDRAMAYU - Ratna Dewi Lestyorini (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2019)
This study aims to determine the existence of a positive relationship between the skill of teachers with student learning interest in SDN Pagirikan 1 Pasekan Indramayu. This research is a qualitative research with correlation research design. The population of this study is 164 students and the sample of research is the high class; class IV, V, VI; 84 students. The result of this research can be concluded that there is a positive relationship between teachers' teaching skills with the students learning interest in high class in SDN Pagirikan 1 Pasekan Indramayu. From this reasearch can be saw that each teacher has different skills in accordance with the subjects taken. By way of increasingly creative teaching, the student's interest in learning is also higher, so it can produce value above the KKM.